Social Work and policy practice: group reflection and policy inquiry - Tony Evans (Social Work and Society, 2022)
Social policy in social work can be taught as rules articulated in documents.  But the policy work in professional practice is more complex - it involves not only knowing what policy says but also how it works and how to make it work. Social work tends to be located within street-level organisations where policy and its implementation are iterative and interlinked. It's a context where policy is found not only in documents but also in the level of finance, organisational structures, and the deployment of human resources.